Seth on Mount Sinai: A Coptic Magical Formulary with a Prayer and Theophany of the Biblical Seth - Zellmann-Rohrer, Michael (Zeitschrift für ägyptische Sprache und Altertumskunde, 2017)
Edition of an unpublished Coptic magical papyrus with formulae for prayers and an amulet for divine protection and assistance. The first of the prayers bears witness to the adaptation of Jewish post-biblical lore for Coptic magic, via the intermediary of Greek translation. The papyrus, probably to be dated to the fifth or sixth century CE, was found in excavations at Lisht.